Implementasi Algoritma Boyer-Moore untuk Otomatisasi Penyaringan Teks Konten Negatif pada Naskah Buku Anak - Yogi Maulana (TIN: Terapan Informatika Nusantara, 2026)
The advancement of digital media increases the risk of exposure to negative content in children’s books, while manual curation in educational institutions is hampered by inefficiencies. This study implements the Boyer-Moore algorithm integrated with Regular Expressions (Regex) to automate text screening based on the quality standards of Ministry of Education, Culture, Research, and Technology Regulation No. 22 of 2022. This study contributes by providing a Regex integration scheme as a pre-processing component that dynamically normalizes variations in obfuscated text before execution by the Boyer-Moore character-jumping mechanism, an approach that has not been widely explored in regulatory manuscript filtering systems. Test results on 40 documents show that the system achieves a 95% success rate specifically in detecting exact matches of prohibited words listed in the database, with an average execution time of 0.000107 seconds per document. These results demonstrate that this combination of methods provides a highly efficient technical solution for reducing the initial curation workload, although its implementation is still limited to a dictionary-based approach and does not yet incorporate semantic context understanding.